STRATEGY OF THE POLITICAL CAMPAIGN MODEL : Study of the Phenomenon of Female Candidates in Blitar District - Andiwi Meifilina; Sulistyo Anjarwati (Universitas Islam Balitar, 2019)
The problems faced when approaching the election are many, one of which is the problem related to how to lobby politics to the public to use their voting rights so that they do not abstain. This problem that is often encountered can be solved by implementing the right political campaign model strategy. The strategy in political campaigns is a careful plan for activities to achieve specific goals where the activities carried out are carried out by political organizations or competing candidates to compete for positions in parliament in order to get the support of the mass of voters (voters) in voting. In line with Law No. 10 of 2008 concerning elections for members of the DPR, DPD and DPRD loaded with 30 percent quota for women in article 53, coupled with article 8 paragraph 1 mentioned regarding statements of at least 30 percent quota of women's representation in central party political party management as one of the requirements political parties to be able to become participants in the election. The purpose of this study was to find out in depth about the strategy of the political campaign model of female candidates in Blitar Regency as a method used by legislative candidates to attract their voters. This way of lobbying politics to the community has the aim of introducing candidates to the public through political campaigns that bring up the positive image of legislative candidates by involving the community. One way in which legislative candidates take to attract attention and get votes from various communities is starting from giving promises when campaigning. The subject of this research is that all the people and female candidates in Blitar Regency and the object of their research are the political campaign model strategies in Blitar Regency. The type of research used is qualitative research using the phenomenology approach. The phenomenology approach aims to describe the meaning of life experiences experienced by some individuals about certain concepts or phenomena by exploring the structure of human consciousness. So here the researcher wants to know the meaning of the experience experienced by the community and female candidates related to the political campaign model strategy through this phenomenology study. This research method uses a qualitative approach with interviews, observation, and documentation studies. This research produced a strategy model for political campaigns related to the phenomenon of female candidates in Blitar District.